Antiangiogenic and antioxidant in vitro properties of hydroethanolic extract from açaí (Euterpe oleracea) dietary powder supplement - Costa, Raquel (2022)
The Euterpe oleracea fruit (açaí) is a promising source of polyphenols with health-promoting properties. To our knowledge, few studies have focused on the influence of açaí phytochemicals on angiogenesis, with a significant impact on cancer. This study aimed at investigating the phytochemical profile of a purple açaí hydroethanolic extract (AHE) obtained from a commercial dietary powder supplement by high-performance liquid chromatography coupled to diode array detection and electrospray ionization mass spectrometry, and evaluate its in vitro effects on distinct angiogenic steps during vessel growth and on oxidative markers in human microvascular endothelial cells (HMEC-1). The phenolic profile of AHE revealed the presence of significant levels of anthocyanins, mainly cyanidin-3-O-rutinoside, and other flavonoids with promising health effects. The in vitro studies demonstrated that AHE exerts antiangiogenic activity with no cytotoxic effect. The AHE was able to decrease HMEC-1 migration and invasion potential, as well as to inhibit the formation of capillary-like structures. Additionally, AHE increased antioxidant defenses by upregulating superoxide dismutase and catalase enzymatic activities, accompanied by a reduction in the production of reactive oxygen species. These data bring new insights into the potential application of angiogenic inhibitors present in AHE on the development of novel therapeutic approaches for angiogenesis-dependent diseases.